Characteristics and Outcomes of Patients on Tofacitinib for Alopecia Areata or Rheumatoid Arthritis: A Retrospective Cohort Study - Sarah Choe; Abhinav Birda; Jesse Salas; Olive Anagu; Natasha Mesinkovska (MDPI AG, 2024)
Tofacitinib is a Janus kinase inhibitor (JAKi) that is used off-label for the treatment of alopecia areata (AA). Its boxed warning includes an increased risk of serious adverse events (SAEs) based on the results of a safety trial in rheumatoid arthritis (RA) patients taking the medication. The purpose of this study was to investigate the differences in patients' characteristics and SAEs profiles between RA and AA populations taking tofacitinib. The cohorts were constructed using the TrinetX database to identify the patients who were prescribed tofacitinib for RA or AA between October 2012 and October 2023. A total of 22,873 patients were included in this analysis, with 21,080 individuals in the RA cohort and 1793 individuals in the AA cohort. After matching for age, sex, and race, each cohort had a sample size of 1482. Data on the patients' sex, age, race, comorbidities, concomitant medications, and associated SAEs were collected. The cohorts were compared by calculating the odds ratios and tested for significance associations using Fisher's Exact Tests. Both the RA and AA cohorts were predominantly female (RA 79%, AA 70%), with mean ages of 61 ± 14 years and 38 ± 19 years (p-value < 0.0001), respectively. Both the groups showed similar racial distributions. The RA cohort had increased rates of hypertension, obesity, type 2 diabetes mellitus, and nicotine dependence compared to those of the AA cohort (p-value < 0.0001). With the exception of cyclosporine and azathioprine, the percentage of concomitant medication use was higher in all the categories in the RA cohort than those in the AA cohort (p-value < 0.0001). Higher rates of adverse events were seen in the RA cohort across all the categories, except myocardial infarction, stroke, and lymphomas/hematopoietic malignancies. Our findings show that the SAEs on the boxed warning of tofacitinib should be strongly considered when being used off-label for the treatment of AA. Clinicians must carefully assess the individual patient factors when determining the appropriateness of tofacitinib use.